COULD EARNING MANAGEMENT MODERATE THE EFFECT OF CSR, GCG AND LEVERAGE TOWARDS TAX AGGRESIVENESS? - Nidia Putri Amelia; Hadri Mulya (Dinasti Publisher, 2022)
Tax is the biggest income in Indonesia, however taxpayers assume that tax is an additional expense for corporate so that taxpayers carry out tax aggressive behavior in order to reduce their tax expense. Purpose of this research is to test empirically the effect of CSR disclosure, leverage, and GCG disclosure towards tax aggressiveness moderated by earning management in mining industry registered in the Indonesian stock exchange for the period 2014-2019. Method of sample selection used purposive sampling and obtained 14 corporates with observations total of 84. Panel data regression analysis applied in this study used the help of Eviews version 12. Based on the results of hypothesis test, it is stated that the corporate social responsibility disclosure, leverage and good corporate governance disclosure have no effect on tax aggressiveness. Likewise, after being moderated by earning management, the results show that earning management is not able to moderate the effect of disclosure of corporate social responsibility towards tax aggressiveness, while earning management is able to moderate the effect of leverage and good corporate governance disclosure towards tax aggressiveness.